Features of plasma formation for SNF magnetoplasma reprocessing at ionization stage - Katrechko, V.V.; Yuferov, V.B.; Svichkar, A.S.; Tkachova, T.I.; Shariy, S.V.; Ilichova, V.O. (Вопросы атомной науки и техники, 2016)
Stage ionization is an intermediate stage separation of spent nuclear fuel (SNF) between heating stage and magnetoplasma separation of fission products (FP) and nuclear fuel (NF) in rotating plasma. The process of plasma formation involving actinides and lanthanides that will remain in SNF after heating stage by way of example U/La is considered. The influence of mixture percentage composition and value of mirror ratio of magnetic field on the ratio U⁺ /La⁺ is investigated. It is shown that it is preferable to operate with low temperature plasma to improve the separation that is considerably for reducing of U²⁺ formation Стадия ионизации является промежуточной стадией разделения отработанного ядерного топлива (ОЯТ) между стадией нагрева и магнитоплазменным разделением продуктов деления (ПД) и ядерного топлива (ЯТ) во вращающейся плазме. Рассмотрен процесс создания плазмы, включающей актиноиды и лантаноиды, которые останутся в ОЯТ после стадии нагрева, на примере смеси U/La. Исследовано влияние процентного состава смеси и величины пробочного отношения магнитного поля на соотношение U⁺ /La⁺. Показано, что низкотемпературная плазма имеет предпочтение для улучшения сепарации, что также существенно для уменьшения образования U²⁺. Стадія іонізації є проміжною стадією розділення відпрацьованого ядерного палива (ВЯП) між стадією
нагріву і магнітоплазмовим розділенням продуктів поділу (ПП) та ядерного палива (ЯП) в плазмі, що
обертається. Розглянуто процес створення плазми, що включає актиноїди і лантаноїди, які залишаться в
ВЯП після стадії нагріву, на прикладі суміші U⁺ /La⁺. Досліджено вплив процентного складу суміші та
величини пробкового відношення магнітного поля на співвідношення U⁺./La⁺. . Показано, що
низькотемпературна плазма має перевагу для поліпшення сепарації, що також істотно для зменшення
утворення U²⁺.